Treatment of Phimosis Without a Knife in Children - Deshpande, Aditi; Dighe, Durva; Patil, Arya (Journal of Neonatal Surgery, 2024)
Aims & Background:The aim of this study was to analyse the efficacy of conservative management for phimosis, and which grade showed the most significant response for the same. Materials and Methods: In this retrospective study, patients were divided into mild and severe groups at 1st presentation. All were managed conservatively with topical Mometasone and Sitz baths. Parental education on prepuce hygiene and gentle retraction was emphasized. At the end of 6 weeks depending on response to this conservative treatment groups of responders and non-responders were made for analysis. Results:Mild phimosis group showed complete and almost complete resolution with conservative management. Severe phimosis group showed significant downgrading in first follow-up and almost complete resolution by second follow-up at 6 weeks. Conclusion:This study emphasizes conservative management as the first-line treatment for phimosis, especially in paediatric populations, to avoid the risks of desensitization and functional loss associated with surgery apart from general anaesthesia complications. Clinical significance: The importance of conservative management as opposed to invasive procedure even for grades of phimosis that are usually managed surgically first. It is not only cost effective, provides lesser hospital stay for patients and has lesser side effects for the same.